SISTEMAS FISIOGRÁFICOS DEL ÁREA NATURAL PROTEGIDA “VALLE CRETÁCICO”, PROVINCIA DE RÍO NEGRO - Romina Solorza; Marcos D. Mare (Boletín Geográfico, 2011)
The demographic expansion of cities in the Alto Valle and the regional tendencies for social practices of leisure and recreation, mark an increasing preference of population towards the surrounding rugged landscape and the consequent increase in the load pressure on semi-arid and sparsely anthropied environments of the south margin of the rivers Limay and Negro. As an example, it is enough to mention the practice of not regulated sport activities that are aggressive for environment, which contribute to accelerate erosion processes, loss of vegetation and soils, etc., while the unplanned urban development characterized by the lack of basic services in the suburbs, has led to a high rate of extraction of wood resources of the bush, the emergence of unauthorized micro rubbish dumps, greater frequency in the fire occurrence, etc. Given this context, the Rio Negro provincial government has materialized in 2010 an old regulation initiative aimed at sustainable management of those lands. This paper is a revised and shortened version of the biophysical studies of carried out as a part of the interdisciplinary technical reports for the "Management Plan of the Protected Natural Area (PNA) Cretaceous Valley" of the Rio Negro Province. The physiographic systems study shows that there is a marked susceptibility to the erosion processes increase, especially gully erosion. The natural vegetation, as a consequence of its physiognomic characteristics adapted to semiarid and mesothermal climate and of the historical social land use overloading , currently presents a low coverage, associated with low levels of soil aggregation. This is the starting point to explain the most obvious features of land degradation in the area. The approach with a perspective oriented to the dynamic nature of natural processes, contributes to the goal of designing proposals for conservation, remediation and management of resources in terms of a sustainable landscape and cultural appropriation by the regional society.